Soil quality in the Huetar Atlantic region of Costa Rica: A comparison between two banana production conditions and a secondary forest - Vargas-Fernández, Jose Pablo (2025)
Introduction. The decline in soil quality affects the sustainability of banana production. Improving limiting soil factors increases its quality and ensures the sustainability of production. Objective. To compare soil quality under high (AP) and low (BP) productivity conditions, and a mature secondary forest (BM) in the Huetar Atlántica region of Costa Rica, using soil quality indicators and indexes. Materials and methods. Chemical, physical, and biological soil indicators, as well as plant biometrics (ICS), were analysed. The quality assessment included: the formation of indicator sets, interpretation and score assignment, and integration into soil quality indices (InCS) by a simple additive approach. The indicator sets assessed were a total set (TDS) and two reduced sets, based on principal component analysis (MDSPCA) and expert criteria (MDSEO). The SMAF and CND methodologies interpreted the ICS, assigning scores between 0 and 1 based on local cultivation conditions. Results. The InCS indicated better quality in AP and BM than in BP. BP showed compaction up to 100 cm depth and higher concentrations of macro and micronutrients, but lower total organic carbon and pH. BM and AP showed higher biological activity than BP. AP excelled in biometric and root system indicators, while BP stood out for foliar concentrations of Ca and Mg. Conclusions. The MDSPCA and MDSEO sets were more sensitive than the TDS in differentiating soil quality, due to lower redundancy and subjectivity. The SMAF and CND methodologies were consistent, but their application depends on specific conditions and the availability of regional data. The integrated approach used in this study optimized soil quality assessment and supports the sustainability of banana cultivation.